Legalitas Pemerintah Daerah Dalam Memberikan Bantuan Dana Kepada Perguruan Tinggi di Indonesia - Komang Satria Wibawa Putra (Fakultas Hukum, Universitas Warmadewa, 2020)
The existence of tertiary institutions spread throughout Indonesia requires the role of local governments in providing financial assistance. Article 83 paragraph (2) of the Higher Education Law provides that regional governments can provide support for Higher Education funds allocated in the Regional Revenue and Expenditure Budget. The norm in the article results in multiple interpretations related to when and how local governments provide financial assistance. So the formulation of the problem used is 1) How is the legality of the local government in funding tertiary institutions in Indonesia? 2) What is the role of local government in providing financial support to universities in Indonesia? The research method used in this study is the normative legal research method. The results showed that seeing the position of tertiary institutions within the local government environment as Regional Assets, Strategic Partners and the Center of Excellent, created very favorable situations and conditions for local governments to synergize with tertiary institutions. In addition, the meaning of the word can be in Article 83 paragraph (2) of the Higher Education Act is interpreted as a situation of local governments that are able, able or able to provide financial assistance to universities. If the regional government feels unable, able or able, then the allocation of funds to the tertiary institution may not be carried out. Then the ability can be played by the government as a regulator, dynamic and facilitator.